Perancangan Desain Packaging Untuk Aksesoris Pernikahan Wedding Planner Dodok Lawang Banyumanik Semarang - nugroho, setiyo adi; Yulfiani, Rizka Amalia; Zaenudin, Ahmad; rudjiono, rudjiono (UNIVERSITAS STEKOM, 2023)
Product packaging has a very important role in attracting consumers, making consumers select the goods and serving as a tool for brand promotion. Using images, colors, and text, graphic designers can apply design principles to produce visually appealing packaging, highlight the benefits of a product, and give it a unique personality. Dodok Lawang runs a business in the form of services, namely making dowries, gifts, ring boxes and gift boxes. In this research, we developed packaging making/with the aim of renewing old packaging so that it appears more attractive. The form of packaging for the wedding planner is in the form of boxes and paper bags, as well as leaflets with a simple but still elegant design concept. validation from media experts and material expert have a result that the product is valid to be used as a protecting/wrapping of product properly. From the user's side, this design is effective because the information and visuals acquired from the packaging design are better understood by the user.